Criminal Act Principles Policy Renewal of Criminal Act in Indonesia - Sidik Purnama (Jurnal Daulat Hukum, 2018)
After Indonesia's independence, some legal experts Indonesia tried to make the Criminal Code itself in accordance with the characteristics of Indonesia based on Pancasila and legal values that live and thrive in Indonesian society, but the spirit of the legal experts of the Indonesian nation was not offset by a member legislative duty during the Old Order, New Order and the Reform Era. It was only during the reign of President Joko Widodo draft Act, especially criminal Act book on a book I had been passed in 2018 this with legalized the Draft Penal Code Book I into Act by the legislative period 2014 - 2019 will automatically bill the Penal Code which has been stalled for more than 56 years, has now become a legitimate Act although not enrolled gazetted in Indonesia. This research method using normative juridical approach. The results showed that essentially the principles and foundations of the criminal Act system and the colonial criminal Act still survive with a blanket and face Indonesia. Principles of criminal Act enactment space according to Criminal Code draft concept consisting of: according to time and according to place. The meaning and nature of criminal Act reforms can be divided into two parts: from the point of policy approaches; and on the angle of approach valuesKeywords: Policy of Positive Criminal Act; Criminal Act Reform.